Pendampingan Pembuatan Lampu ‘LAMPIAS’ (Lampion Hias) Di Kecamatan Biringkanaya Kota Makassar - Mustari Mustari; Nurjannah Nurjannah; Nur Arisah; Andi Michlis Sirajuddin; Lestari Wulandari (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This article aims to assist the community in making LAMPIAS lamps (decorative lanterns) in Biringkanaya District, Makassar City so that they can have high economic selling value and it is hoped that they can be marketed and as a learning medium for these products. Apart from that, through this assistance, producing a product that can be marketed can help the consumer community by fulfilling the desire for unique goods so that this product can be of interest to many groups and citizens. People need quality and unique items that can help create a comfortable and beautiful atmosphere indoors. It is hoped that these decorative lantern lights will have enthusiasts and buyers who are looking for this product. In this activity, the method we use is to provide assistance in making LAMPIAS lamps (decorative lanterns) to the community in Biringkanaya District, Makassar City and offer creativity by exploring new shapes with a variety of colors and patterns to make them more attractive and adaptable to consumer needs. This is due to a decrease in interest in the shapes and color variations of old ordinary lamps and we make them in more attractive shapes so that more people buy and like decorative lanterns again and use them as something that can decorate the interior of the house.